Itinérance et métissage : pour une littérature qui se réinvente - Lohka, Eileen (Romanica Silesiana)
Nomadism and hybridity (métissage) are two keys words when it comes to Creole island societies. J.M.G. Le Clézio, Édouard Maunick and Ananda Devi of Mauritius all explore memory and language to erase (often constructed) boundaries between past and present, reality and the imaginary, land and sea, French and Creole. It is a way to transgress literary canons. Their poetics favour liminal spaces, a plurality of voices and meanings and an openness to the Other that may offer a new way of reading works written in the in‑between space of exile — a condition becoming more and more common in today’s globalised world. Key words: Mauritian Francophone Literature; nomadism; hybridity; poetics of liminality